Effects of Limestone Characteristic Properties and Calcination Temperature on Lime Quality - Kilic, Ozen; Anil, Mesut (Asian Journal of Chemistry, 2010)
This study has examined the effects of limestone characteristics (microstructure and texture) and calcination temperature on the quality of the produced lime. Two types of limestone have been studied for physico mechanical properties and calcined at selected temperatures (650, 700, 750, 800, 850, 900, 950, 1000, 1050 and 1200ºC). Chemical, physico-mechanical and mineralogical analyses have been performed in limestone samples, determing lime quality and reactivity. Test results indicate that higher the limestone calcination temperature (950 and 1000ºC), the more reactive the produced lime. Concerning the lime, the reactivity is related to its impurities and microstructure, which is, in turn, related to microstructural characteristics of the limestone (texture, grain size, porosity). The most reliable factors for the estimation of lime reactivity are the specific surface area, porosity and hydration rate (T60) of the lime and the temperature during the calcination process.